Blades have the edge [blade servers]. - Wright, J. (IEEE spectrum)
An increasing number of computer rooms all over the world are switching from conventional servers to blade servers because they offer huge improvements over conventional, rack-mounted units. The greatest benefit of blades is their flexibility, which allows them to be easily installed, managed and repaired compared to conventional servers. The promise of blades lies not so much in their hardware as in the software used to manage them. Blades' management programs let system administrators automate and simplify what are otherwise tedious, time-consuming tasks. Another useful feature manufacturers are adding to blades is the ability to split a single physical blade server into many smaller, virtual ones. This allows an administrator to create logical shells that each run a different operating system and its respective applications simultaneously on a single server.